The Psychometric Properties of the Norwegian version of Brown Attention-Deficit Disorder Scales for Children and Adolescents, 8-12 years (Brown ADD 8-12) - Hysing, Mari; Bøe, Tormod (PsykTestBarn, 2012)
Description: Brown ADD scales (8-12) is an instrument that measures a broad spectrum of ADHD-symptoms and functional impairments in executive functions related to ADHD in schoolaged children. The instrument is developed by Tomas E. Brown, and there is an official Norwegian translation by Tone M. Anderssen available from Pearson Assessment. The instrument may be used as an interview with parents/caretakers, but may also be administered as a questionnaire to other informants. The instrument has 44 items and can be completed in less than 30 minutes. Only psychologists with testing competency may administer the instrument. Literature search: The literature search did not identify any studies that met the inclusion requirements. Psychometrics: None of the identified studies documented the psychometric properties of the Norwegian version of Brown ADD scales (8-12). Conclusion: The psychometric properties of the Norwegian version of Brown ADD scales (8-12) are not documented.